Utilization of Digital Influencer Strategy in Improving the Image of Hotel ‎Savoy Homann Bandung - Rizky Amelia (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
In the current digital era this, industry hospitality sued for keep going adapt with development technology and change behavior consumers. One of the modern marketing strategies that is starting to Lots used is utilization of digital influencers, namely individuals who have influence big on social media and capable influence opinion public. Research this aiming for know how far can a digital influencer strategy go? increase image of Savoy Homann Hotel in Bandung City. Research this done with method studies library, using approach descriptive qualitative. Research results show that utilization of digital influencers can strengthen hotel branding, improve visibility on digital platforms, as well as build trust and loyalty Customers. Research This expected can become reference for perpetrator industry hospitality in develop more marketing strategies​ effective and relevant with current development .